1994
DOI: 10.1038/ki.1994.226
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of peritoneal transport in CAPD patients

Abstract: A prospective two year follow-up study of the functional characteristics of the peritoneal membrane was conducted in 61 CAPD patients. Peritoneal transport of solutes, calculated by mass transfer area coefficients for urea and creatinine, peritoneal clearances for proteins, percentage of absorption of glucose, as well as net ultrafiltration were measured every four months. After five months on CAPD a decrease was found for the transport of most solutes (P < 0.05, mean values, ml/min/1.73 m2): urea 18.1 to 16.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 38 publications
9
76
2
Order By: Relevance
“…There are several possible explanations. First, a relationship with increasing age, as described previously (8)(9)(10), was seen in the patients treated for 2 and 3 years (see Supplemental Table 2), and this could account for some hidden association with comorbid disease. Second, this is a deliberately selected patient cohort and patients with more serious comorbidity-or specific types, such as peripheral vascular disease-were under-represented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several possible explanations. First, a relationship with increasing age, as described previously (8)(9)(10), was seen in the patients treated for 2 and 3 years (see Supplemental Table 2), and this could account for some hidden association with comorbid disease. Second, this is a deliberately selected patient cohort and patients with more serious comorbidity-or specific types, such as peripheral vascular disease-were under-represented.…”
Section: Discussionmentioning
confidence: 99%
“…This relative reduction in large-pore area could reflect many processes, including a resolution of the early inflammatory state of the membrane after the start of PD. Several studies have also shown that depending on when the initial membrane function tests are done, PSTR also decreases in the months after PD is established before the longer-term increase (10,(18)(19)(20)(21). Alternatively, it could mean that large pores are underrepresented in newly formed vessels (surprising because new vessel formation in diabetic nephropathy is associated with increased protein extravasation) or that interstitial and perivascular fibrosis, known to occur over time (1), is impeding large-pore leak through the interstitial structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, malnutrition and chronic inflammation are prevalent in high transporters (29)(30)(31)(32). Low serum albumin level correlates with malnutrition (28) and is strongly predictive of PD patient mortality (29,30). The greater prevalence of hypo-albuminemia in high transporters may also arise from hemo-dilution secondary to suboptimal ultrafiltration (31) or from excessive peritoneal protein losses (32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed high transport status to be associated with poor survival in PD patients (11,28). Moreover, malnutrition and chronic inflammation are prevalent in high transporters (29)(30)(31)(32). Low serum albumin level correlates with malnutrition (28) and is strongly predictive of PD patient mortality (29,30).…”
Section: Discussionmentioning
confidence: 99%